Judicial Discretion in Corporate Bankruptcy - Gennaioli, Nicola; Rossi, Stefano (Review of Financial Studies, 2010)
[We study a demand-and-supply model of judicial discretion in corporate bankruptcy. On the supply side, we assume that bankruptcy courts may be biased for debtors or creditors, and subject to career concerns. On the demand side, we assume that debtors (and creditors) can engage in forum shopping at some cost. A key finding is that stronger creditor protection in reorganization improves judicial incentives to resolve financial distress efficiently, preventing a "race to the bottom" toward inefficient uses of judicial discretion. The comparative statics of our model shed light on a lot of evidence on U.S. bankruptcy and yield novel predictions on how bankruptcy codes should affect firm-level outcomes.]